Step
*
2
of Lemma
finite-Ramsey1
1. c : ℕ
2. ∀c:ℕc. ∀s:ℕc ⟶ ℕ.
     ∃N:ℕ+
      ∀g:ℕN ⟶ ℕN ⟶ ℕc. ∃i:ℕc. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
3. s : ℕc ⟶ ℕ
4. ¬(c = 0 ∈ ℤ)
⊢ ∃N:ℕ+
   ∀g:ℕN ⟶ ℕN ⟶ ℕc. ∃i:ℕc. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
BY
{ CaseNat 1 `c' }
1
1. c : ℕ
2. ∀c:ℕc. ∀s:ℕc ⟶ ℕ.
     ∃N:ℕ+
      ∀g:ℕN ⟶ ℕN ⟶ ℕc. ∃i:ℕc. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
3. s : ℕc ⟶ ℕ
4. ¬(c = 0 ∈ ℤ)
5. c = 1 ∈ ℤ
⊢ ∃N:ℕ+
   ∀g:ℕN ⟶ ℕN ⟶ ℕ1. ∃i:ℕ1. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
2
1. c : ℕ
2. ∀c:ℕc. ∀s:ℕc ⟶ ℕ.
     ∃N:ℕ+
      ∀g:ℕN ⟶ ℕN ⟶ ℕc. ∃i:ℕc. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
3. s : ℕc ⟶ ℕ
4. ¬(c = 0 ∈ ℤ)
5. ¬(c = 1 ∈ ℤ)
⊢ ∃N:ℕ+
   ∀g:ℕN ⟶ ℕN ⟶ ℕc. ∃i:ℕc. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
Latex:
Latex:
1.  c  :  \mBbbN{}
2.  \mforall{}c:\mBbbN{}c.  \mforall{}s:\mBbbN{}c  {}\mrightarrow{}  \mBbbN{}.
          \mexists{}N:\mBbbN{}\msupplus{}
            \mforall{}g:\mBbbN{}N  {}\mrightarrow{}  \mBbbN{}N  {}\mrightarrow{}  \mBbbN{}c
                \mexists{}i:\mBbbN{}c.  \mexists{}f:\mBbbN{}s  i  {}\mrightarrow{}  \mBbbN{}N.  (Inj(\mBbbN{}s  i;\mBbbN{}N;f)  \mwedge{}  (\mforall{}a,b:\mBbbN{}s  i.    (f  a  <  f  b  {}\mRightarrow{}  ((g  (f  a)  (f  b))  =  i))))
3.  s  :  \mBbbN{}c  {}\mrightarrow{}  \mBbbN{}
4.  \mneg{}(c  =  0)
\mvdash{}  \mexists{}N:\mBbbN{}\msupplus{}
      \mforall{}g:\mBbbN{}N  {}\mrightarrow{}  \mBbbN{}N  {}\mrightarrow{}  \mBbbN{}c
          \mexists{}i:\mBbbN{}c.  \mexists{}f:\mBbbN{}s  i  {}\mrightarrow{}  \mBbbN{}N.  (Inj(\mBbbN{}s  i;\mBbbN{}N;f)  \mwedge{}  (\mforall{}a,b:\mBbbN{}s  i.    (f  a  <  f  b  {}\mRightarrow{}  ((g  (f  a)  (f  b))  =  i))))
By
Latex:
CaseNat  1  `c'
Home
Index